SGLT2 Inhibitors and nephroprotection in diabetic kidney disease: From mechanisms of action to the latest evidence in the literature - Rico-Fontalvo, Jorge; Daza-Arnedo, Rodrigo; Cardona-Blanco, Maria Ximena; Leal-Martínez, Victor; Abuabara-Franco, Emilio; Pajaro-Galvis, Nehomar; Cabrales, Jose; Correa, José; Cueto, Manuel; Duran, Amable; Castellanos, Alejandro; Enamorado, Javier; et al. (Journal of Clinical Nephrology, 2020)
Type 2 Diabetes Mellitus constitutes a major problem in public health worldwide. The disease poses a high risk of severe microvascular and macrovascular complications. Diabetic kidney disease is the most common cause of end-stage chronic kidney disease and contributes to the increasing morbidity and mortality associated to diabetes. Sodium-glucose contransporter-2 inhibitors (SGLT2 inhibitors) are the latest oral diabetic medications, which exhibit a great nephroprotective potential, not only by improving glycemic control, but also by glucose-independent mechanisms, such as decreasing blood pressure and other direct renal effects. We conduct a literature review based on the most recent scientific evidence with the goal to elucidate the postulated mechanisms of action of SGLT2 inhibitors in diabetic kidney disease, which are the base of the beneficial clinical effects that are seen in the condition.